PERAN PEMBIMBING KEMASYARAKATAN TERHADAP NARAPIDANA BEBAS BERSYARAT YANG MELAKUKAN TINDAK PIDANA DI BALAI PEMASYARAKATAN KLAS II PEKANBARU - Futri, Shofiyana; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The role of social counselor has an important role in providing guidance to the inmates who have gained parole, by giving special guidance and scrutiny. The shape of the guidance given manifold, ranging from the provision of guidance on the religious, skills, to the personality development. Guidance providing is done to the clients correctional does not undertake criminal anymore, become a better person and be accepted in society. The purposes of this thesis are: First, to know the role of social counselor for parole inmates who committing criminal in the Correctional Center Class II Pekanbaru. Second, to explain the obstacles that faced by the social counselor for parole inmates who committing criminal in the Correctional Center Class II Pekanbaru. Third, to show the efforts made towards social counselors parole inmates who committing criminal in Correctional Centers Class II Pekanbaru.The research is a sociological study, the research was conducted in the Correctional Central Class II Pekanbaru. The population and the sample is all parties involved with the problems examined. Sources of data used are: primary data, secondary data and data tertiary, technical data collection using interviews, questionnaires and review of the literature.Based on this research there are three main issues that can be inferred. First, the role of social counselor for parole inmates who committed the crime in the Correctional Central Class II Pekanbaru has not run optimally. Second, the obstacles that faced by social counselor for parole inmates who committing criminal in the Correctional Central Class II Pekanbaru namely: lack of personnel, facilities and infrastructure, environmental factors, economic factors, the dependency of inmates, Third, efforts made by social counselor the to overcome for parole inmates who committing criminal in the Correctional Central Class II Pekanbaru, increasing the number of personnel, completed the facilities and infrastructure, organize seminar for social counselor. Writer suggest three things, first required the addition of personnel in the Correctional Central Class II Pekanbaru. Second, social counselor should pay more attention to internal or external issue. And social counselor should firmly and precisely take a stand.